2006
DOI: 10.1203/01.pdr.0000200806.32822.e6
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B/Pulmonary Surfactant Mixtures Have Increased Resistance to Inactivation by Meconium and Reduce Growth of Gram-Negative Bacteria In Vitro

Abstract: Pulmonary surfactant is inactivated in meconium aspiration syndrome and neonatal pneumonia. Development of an exogenous surfactant less sensitive to inactivation might be useful for treating these diseases. We investigated in vitro whether addition of the cationic cyclic membrane cross-linking peptide polymyxin B (PxB) and/or calcium chloride (CaCl 2 ) to modified porcine surfactant Curosurf increases resistance to meconium-induced inactivation of surface activity while antimicrobial activity of PxB is maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…However, our previous studies demonstrated that addition of PxB to modified pSF increases resistance to surfactant inactivation and maintains antimicrobial activity of PxB (6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, our previous studies demonstrated that addition of PxB to modified pSF increases resistance to surfactant inactivation and maintains antimicrobial activity of PxB (6).…”
Section: Discussionmentioning
confidence: 92%
“…Our group previously found that addition of PxB to modified porcine surfactant (pSF) increases resistance to meconiuminduced surfactant inactivation in vitro while the antimicrobial function of PxB is maintained (6). Thus, the combination of PxB and surfactant might be useful in clinical conditions such as neonatal Gram-negative pneumonia, MAS, or ARDS.…”
Section: P Olymyxins Are Cyclic Antimicrobial Peptides Derived Frommentioning
confidence: 99%
“…We previously showed that addition of PxB to porcine SF in vitro resulted in maintained antimicrobial activity and improved surface activity [8]. In addition, PxB accelerates SF exocytosis in isolated cultured rat alveolar type II cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…The use of SF as a vector for topical pulmonary drug administration is a concept that has been evaluated for mixtures with antibiotics [6,7], including polymyxin B (PxB) [8]. Polymyxins and SF-specific proteins B and C have some similar properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a group of additives capable of decreasing surfactant inactivation is under investigation, showing promising results. These include chitosan [153], hyaluronan [91,92,141], dextran [108] and polymyxin B [27,130]. The potential of these additives lies in their use in RDS and meconium aspiration syndrome (MAS), where inactivation of surfactant by albumin and meconium respectively decreases its efficiency.…”
Section: Synthetic Surfactantmentioning
confidence: 99%